Physical layer security performance of SWIPT system in the presence of randomly located eavesdroppers - Hui QIAN; Guangqiu LI; Yifan DING (Dianxin kexue)
The locations of the eavesdroppers have serious impact on the physical layer security performance of simultaneous wireless information and power transfer (SWIPT) systems with transmit antenna selection (TAS) and power split (PS) strategy,which can be considered to be modeled as Poisson point process (PPP).The closed-form expressions for secrecy outage probability (SOP) of SWIPT system with TAS and PS strategy under non-colluding and colluding eavesdropping scenarios were derived by using probability generation function of PPP,respectively.Numerical and simulation results show that,the larger the number of transmit antennas,the smaller the distance between the transmitter and the information receiver,and the smaller the PS factor,the smaller SOP of SWIPT system under non-colluding and colluding eavesdropping scenarios.Colluding eavesdropping will further deteriorate the physical layer security performance of SWIPT systems.